ESTABLISHMENT OF CONSTITUTIONAL GUARANTEES OF OPENNESS OF THE ADMINISTRATION OF JUSTICE AS THE BASIS OF THE RIGHT TO A FAIR TRIAL IN CONDITIONS OF ECONOMIC TURBULENCE DUE TO MILITARY ACTIONS - Ihor Zavalniuk (Baltic Journal of Economic Studies, 2022)
The subject of the study is social relations in the field of establishing constitutional guarantees of openness of the administration of justice as the basis of the right to a fair trial in conditions of economic turbulence due to military operations. Methodology. The methodological basis of the study is the methods of induction and deduction, dialectical-materialistic method, method of analysis and synthesis, historical method, which allowed to objectively comprehend the content and essence of the issues under study. The purpose of the article is to study the constitutional guarantees of openness of the administration of justice as the basis of the right to a fair trial in the conditions of economic turbulence due to military operations, and then to propose mechanisms for their effective functioning. The results of the study showed that there are two main types of procedures for the application of constitutional norms in the field of ensuring the right to a fair trial. It seems that the optimization of the application of constitutional norms in the field of ensuring the right to a fair trial involves achieving a balance between these two types of procedures, which ultimately ensure the proper implementation of the constitutional right to a fair trial. Based on the results of the application of the constitutional norm in the field of the right to a fair trial by the courts, two groups of legal consequences of the adoption of acts of application were identified. Conclusions. The idea of justice has been enshrined in the constitutional text as a legal idea rather than a principle of law. At the same time, in modern Ukrainian jurisprudence there is a paradoxical situation when the formally subjective right to a trial has a greater internal content than the principle of "justice" used in various, including procedural, branches of Ukrainian law. Modern Ukrainian legislation rarely operates with the category of "right to a fair trial", but in this case we are dealing with the legitimization at the level of sectoral Ukrainian legislation of the legal construction already established in domestic science and practice, which came from international law, and not an attempt to give the principle of fairness of judicial activity a real formal legal nature. The fact that the modern Ukrainian legislator failed to systematically and conceptually reflect its attitude to the idea of judicial justice in the conditions of the military-economic crisis also has a negative impact on the relevant judicial practice.